Infill masonry : seismic behavior of reinforced solutions - Leite, João C. (2011)
The analysis of buildings constructed in the last 20 years, designed following modern standards, may lead to worrying conclusions. Images of out-of-plane expulsions and in-plane failures of infill walls in recent seismic activities around the world reminded engineers of the consequences of bad practice, wrong solutions or inadequate design. With the above in mind, a research program is being conducted as a partnership between University of Minho and the National Laboratory for Civil Engineering (LNEC), which includes a shaking table experimental program of framed concrete buildings with masonry infill walls, reinforced and unreinforced. Herein the shaking table program and the tested solutions are detailed, along with the discussion of the results, focusing on the local behaviour of the infills and the global behaviour of the concrete structure.